Electrogenerated networks from poly[4-(diphenylamino)benzyl methacrylate] and their electrochromic properties - O. I. Negru; L. Vacareanu; M. Grigoras (eXPRESS Polymer Letters, 2014)
Poly[4-(diphenylamino)benzyl methacrylate] with well-defined molecular weight and low polydispersity was prepared by atom transfer radical polymerization (ATRP) using 4-(diphenylamino) benzyl 2-bromo-2-methyl-propanoate as initiator and CuBr/2,2'-bipyridine as catalytic complex. Electrochemical behavior and optical properties of the polymers were investigated by cyclic voltammetry and UV-Vis and fluorescence spectroscopy. Cyclic votammetric studies revealed that the redox processes were accompanied by dimerization of triphenylamine pendant groups. The initial polymer was postmodified, in solution or bulk, by electrochemical oxidation leading to a crosslinked and insoluble network with electro -chromic properties, accompanied by strong color changes with high coloration efficiency. The crosslinking reaction took place between triphenylamine groups through para free positions leading to tetraphenylbenzidine bridges. The structure of polymers was confirmed by Fourier transform infrared (FT-IR) spectroscopy and 1H and 13C-nuclear magnetic resonance spectroscopy. Morphology studies of the cross-linked film have evidenced a smooth and continuous aspect without any pinholes or defects.